2001
DOI: 10.1007/pl00002431
|View full text |Cite
|
Sign up to set email alerts
|

Recall-Dermatitis durch Docetaxel-Reexposition nach Gehirnbestrahlung Fallbeobachtung und Literaturübersicht

Abstract: The dermatitis related to irradiation and reexposition to Docetaxel observed in our two cases is interpreted as a recall reaction. The basic initiating pathologic mechanism has not been solved completely. Further investigation is needed to find out how the taxanes can be used in combination radiochemotherapy regimens without causing severe toxicity to the irradiated skin or mucosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The dose given by Yeo et al was 100 mg/m 2 every 3 weeks [10]; we used 30 mg/m 2 docetaxel, given weekly. Giesel et al applied 30 and 100 mg/m 2 docetaxel in 2 cases and found comparable skin reactions to the described [4]. In the report by Giesel et al docetaxel was well tolerated before and during radiotherapy.…”
Section: Discussionmentioning
confidence: 66%
“…The dose given by Yeo et al was 100 mg/m 2 every 3 weeks [10]; we used 30 mg/m 2 docetaxel, given weekly. Giesel et al applied 30 and 100 mg/m 2 docetaxel in 2 cases and found comparable skin reactions to the described [4]. In the report by Giesel et al docetaxel was well tolerated before and during radiotherapy.…”
Section: Discussionmentioning
confidence: 66%